PERAN PENDIDIK PAUD DALAM PENINGKATAN KUALITAS PENDIDIKAN DAN PENGEMBANGAN ANAK USIA DINI (PAUD) - Puspita, Widya Ayu (JIV-Jurnal Ilmiah Visi, 2009)
As early childhood education has become a world commitment, its quality in all aspects must be improved continuosly. For this reason, this article discusses specifically the role of the educator in early childhood education. It believes the educators have a strategic role in achieving the objectives of early childhood education.. In instructional process they act as observer, mentor, facilitator and innovator. As an observer, they have a duty to monitor the program and help the children grow optimally. As a mentor, they must improve interaction and communication and motivate the children to learn. As a facilitator, they have to provide assistance to help the children to solve the problems and finally, as an innovator, they have to be creative to make learning enjoyable. If all these role is conducted properly, education climate will be condusive for a better qualty improvement.